Double osseous flaps for simultaneous midfacial and mandible reconstruction: Automation in surgical complexity within an entirely computerized workflow - Tel, Alessandro; Bagatto, Daniele; Sembronio, Salvatore; Ferrari, Silvano; Robiony, Massimo (Frontiers in Oncology, 2023)
Broad maxillofacial surgical resections involving both the midface and the mandible represent a challenge in terms of reconstruction. Microsurgery, which is modernly empowered by digital techniques such as virtual surgical planning and 3D printing, provides a variety of options to address the demanding needs of a functional and aesthetical restoration trough several flaps, which can also be combined in a dual flap strategy. In the last years, the advent of customized maxillofacial implants has become a useful option to simplify reconstructive surgery, especially in association with free flaps. Although several papers have explored the possibility of simultaneously using two microsurgical flaps, reports on the implementation of a dual osseous flap strategy are limited, and tend to privilege anatomical reconstruction over functional implications. In particular, there is a lack in the literature of a unifying protocol which illustrates how technology including virtual planning, statistical shape modeling, virtual occlusion, 3D-printing and patient-specific implants can satisfy the demanding requirements for an accurate reconstruction. In this paper, the Authors present their preliminary experience in a two-center study, showing how broad maxillofacial defects, requiring a simultaneous reconstruction in both the mandible and the midface, can be successfully managed using the combination of two osseous flaps in an automated sequence in which all steps are anticipately defined in a virtual plan, accounting for the optimal alignment of temporomandibular joint, predicting the final occlusion and defining a mandibular shape according to average population variance.